1998
DOI: 10.1097/00043426-199805000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of TEL/AML1 Fusion Transcript in Childhood B-Precursor Acute Lymphoblastic Leukemia

Abstract: This study confirmed that TEL/AML1 gene fusion is the most common genetic event in pediatric ALL in Japan and is restricted to CD10-positive B-precursor ALL. Moreover, it was associated with an improved survival rate among patients treated with intensive therapy. Therefore, these data suggest that the patients with TEL/AML1 may not necessarily be candidates for less aggressive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 16 publications
5
37
0
1
Order By: Relevance
“…This was illustrated in the more recent two treatment protocol, showing that the upfront intensive therapy dramatically improved the outcome in the TEL-AML1-positive children (94% vs 66%) at a median follow-up of 57 months (P = 0.25). A similar observation was recently reported from Japan by Takahashi et al 15 A longer follow-up is required before we can definitively conclude that the current protocal is optimal for TEL-AML1-positive children. An alternative may be to apply the augmented chemotherapy during maintenance therapy.…”
Section: Figuresupporting
confidence: 89%
“…This was illustrated in the more recent two treatment protocol, showing that the upfront intensive therapy dramatically improved the outcome in the TEL-AML1-positive children (94% vs 66%) at a median follow-up of 57 months (P = 0.25). A similar observation was recently reported from Japan by Takahashi et al 15 A longer follow-up is required before we can definitively conclude that the current protocal is optimal for TEL-AML1-positive children. An alternative may be to apply the augmented chemotherapy during maintenance therapy.…”
Section: Figuresupporting
confidence: 89%
“…In Egyptian population, 11.6% frequency of TEL-AML1 transcript was reported in newly diagnosed precursor B-ALL cases of acute lymphoblastic leukemia (Shaker et al, 2001). Frequency of TEL-AML in pediatric ALL patients from Hiroshima Japan was reported to be 10% (Eguchi-Ishimae et al, 1998;Takahashi et al, 1998), while it was reported to be 19% in Nagoya, Japan (Takahashi et al, 1998). Nevertheless, a higher frequency of TEL-AML1 has been reported in pediatric ALL patients in many of the European countries.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that a general intensification of therapy, not only by L-Asp but also by other drugs, might contribute to the fact that in some recent protocols, patients with t(12;21)-positive ALL have a favorable outcome. 27 An intensified treatment protocol may also explain the difference in event-free survival of t(12;21)-positive ALL patients between the DCOG and COALL group (5-year eventfree survival of 73 and 80%, respectively). 28,29 The fact that the prognostic value of t(12;21) positive ALL may depend on the therapy that is being given is further illustrated by the fact that Table 1 Prognostic relevance of genetic changes in TEL and/or AML1 and prednisolone resistance in t(12;21)-positive ALL patients Hazard ratio with 95% CI and P-value of patients being intermediate sensitive or resistant to Prednisolone, compared with the reference group of patients being sensitive to prednisolone.…”
Section: Discussionmentioning
confidence: 99%